KONSEP PAKAIAN JOGJA FASHION WEEK CARNIVAL DALAM STRUKTUR SOSIAL DI YOGYAKARTA - Deni Setiawan (Jurnal Kawistara, 2015)
The Jogja Fashion Week Carnival (JFWC) is related to various agendas of the local government in Yogyakarta, particularly in industrial and tourism sectors. The JFWC event is correlated to the domestic industries in which one of them has a positive impact upon the progress and the existence of this industry in order to reduce the rate of import from outside Yogyakarta. In another domain, the use of public space, which is often done by JFWC event, gives entertainment and cultural education to the people, thus this event is useful and appropriate if it is held as a routine agenda for the existence of the tourism industry in Yogyakarta. The education given to the people includes the global warming issue, the treatment and utilization of hazardous waste, and the important role of JFWC event in an attempt to create clothing trend centre in Yogyakarta. The dialectics of JFWC clothes can be seen as a process of cultural diplomacy locally, nationally, and internationally. In addition, the existence of JFWC clothes can be viewed as a sustainability phenomenon of contemporary artworks in Indonesia.